The Labour of Foreigners and Immigration in Slovenia - Malačič, Janez (Anali PAZU, 2022)
Recent employment of foreigners and immigration in Slovenia are analysed in the paper. The influence of the economic crises is especially stressed. The evidence shows the declining trend of the number of foreign workers in Slovenia in spite of persistence of the demand for foreign labour on labour market in Slovenia.